Synthesis and Characterization of Iron-Doped Lead Sulfide Thin Films - (:unkn) unknown (SPRINGER, 2015)
Thin films have improved the semiconductor device technology because their material characteristics could be changed in many different ways including changing the crystal morphology and size. This study reports manufacturing undoped and Fe-doped nanostructured PbS films on glass substrates by SILAR method. Both undoped and Fe-doped films are examined in terms of structural, optical, and morphological properties via SEM, Uv-vis spectrophotometry, and XRF analysis. Results revealed that all of the thin films were in a face-centered cubic structure and concentration of Fe doping influences the size of the thin film's nanoparticles. The optical band gap of the PbS films decreased as Fe-doping concentration is increased. The intercept values on the energy axis were in the range of 1.66 and 1.25 eV for 1 and 9 pct Fe-doped PbS films, respectively. The structural, optical, and morphological properties of the fabricated thin films directly depend on the Fe-doping ratio.
Keywords: OPTICAL-PROPERTIES; SILAR TECHNIQUE; QUANTUM DOTS; PBS; NANOCRYSTALS; DEPOSITION; SYSTEMS; GROWTH